Experimental investigation on mechanical properties of acetylated birch plywood and its angle-dependence. (15th August 2022) - Wang, Yue; Wang, Tianxiang; Crocetti, Roberto; Wålinder, Magnus
Highlights: A novel modified engineered wood product, namely, plywood made from acetylated birch veneers. Exhaustive dataset of mechanical properties of acetylated birch plywood in tension, compression, panel shear, and edgewise bending. Significant angle dependence of the presented strength and elastic properties. Comparison with ordinary unmodified birch plywood regarding strength, stiffness and failure modes. Abstract: There is an increasing demand for engineered wood products (EWPs) due to the flourish of modern timber structures during recent years. However, the durability-related issues are still unignorable limitations when applying timber to outdoor structures. Therefore, treatment measures are still needed to enhance the durability of timber. The acetylation process, which involves the reaction between acetic anhydride and wood, has been widely studied as a wood modification method during the past decades. Several experimental studies have proven acetylation to effectively reduce wood's hygroscopicity while improving its dimensional stability and fungal decay resistance. For load-bearing timber structures, especially those in the outdoor environment, the combination of acetylation and EWPs gives the possibility to manufacture more durable and stable timber elements in the context of dimensions and mechanical properties. This study concerns the mechanical and elastic properties of acetylated birch plywood. More specifically, tensile, compressive, shear and bending tests were conducted under three different load-to-face grain angles, namely from 0° (parallel), 22.5°, to 45°. The test results were thereafter compared with ordinary unmodified birch plywood concerning stress–strain relationships, failure modes, strength, and elastic properties.